Unveiling the gut-heart potential connection: microbiota’s role in kawasaki disease and coronary artery lesions - Yang, Qing; Tang, Wei; Ren, Jiayu; Li, Meng; Zhao, Cuifen (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundKawasaki disease (KD) is an acute systemic immune vasculitis predominantly affecting medium and small arteries, commonly observed in pediatric patients. It represents the most common form of acquired heart disease in this population. Emerging evidence suggests that gut microbiota can modulate the gut-vascular axis, influencing coronary artery lesions (CALs). This study aims to elucidate the potential association between gut microbiota, KD, and CALs, as well as identify bacterial biomarkers for CALs.MethodsWe analyzed the gut microbiota composition of 60 children with KD (15 in the acute phase, 45 in the nonacute phase) and 30 healthy controls using alpha diversity indices and t-tests. Microbial biomarkers were identified through LEfSe to analyze the interplay between gut microbiota and CALs in KD during acute and non-acute phases.ResultsIn the acute phase, KD children exhibited decreased richness and diversity of gut microbiota, characterized by dysbiosis, particularly a reduction in short-chain fatty acid-producing bacteria and overgrowth of opportunistic pathogens. Thirteen genera showed statistically significant changes, including Enterococcus, Bacteroides, Faecalibacterium, Agathobacter, Lachnospiraceae_NK4A136_group, Roseburia, Monoglobus, etc. LEfSe analysis revealed enrichment of Burkholderia-Caballeronia-Paraburkholderia, Hungatella, and Clostridium_innocuum group in patients with concurrent CALs, while Halomonas was depleted. In the nonacute phase, gut microbiota diversity was similar to healthy controls, but Streptococcus was upregulated, while Eubacterium_eligens_group and Erysipelotrichaceae_UCG_003 were downregulated. CALs were associated with reduced Anaerostipes, Subdoligranulum, Roseburia, and Lachnospira. LEfSe analysis also showed enrichment of Coprobacillus, Paludicola, Lautropia, UCG-009, Acetanaerobacterium, Methylobacterium-Methylorubrum, and Alistipes in patients with CALs.ConclusionsOur findings provide evidence of gut microbiota dysbiosis in KD children, suggesting its involvement in CALs development. It indicates that under the premise of standardized treatment during the acute phase of KD, it is plausible that microbiota-targeted strategies may alleviate CALs, thereby improving patient prognosis.